Belajar Bahasa Indonesia Bagi Penutur Asing (BIPA) Secara Informal: Sebuah Inkuiri Naratif: SEBUAH INKUIRI NARATIF - Kasyfur Rahman (The Center for Language Development, Mataram State Islamic University., 2020)
This paper aims to unveil an American couple’s, Andi and Becky (Psudonyms), experiences when learning Bahasa Indonesia for foreign speakers in Indonesia (BIPA) informally aside from their non- formal learning. They were undertaking a BIPA course hosted by a language center running under a higher education institution. The research in this paper employed a narrative inquiry method of research mainly through interview to cast more light on their informal learning of BIPA. From the findings, it was revealed that they perceived informal BIPA learning as important as the course they were taking and they believed that culture was part of language learning therefore in their views, experiencing it at the natural context would be the best way of learning the culture. Furthermore, when carrying out informal learning to support their BIPA course, they hung out to public place to make exchanges with local people, invited local friends to come home and to help them practice speaking, always took a small notebook of new vocabulary list, the visualization of vocabulary through drawing, writing a journal, listening to Indonesian music, and watching YouTube video. Most of these findings were consistent with the account of sociocultural perspective and situated cognition on learning.